Social structure and forms of consciousness. - Mészáros, István, 1930- (Monthly Review Press, 2011)
In The Dialectic of Structure and History, Volume Two of Social Structure and Forms of Consciousness, István Mészáros brings the comprehension of our condition and the possibility of emancipatory social action beyond the highest point reached to date. Building on the indicatory flashes of conceptual lightning in the Grundrisse and other works of Karl Marx, Mészáros sets out the relations of structure and agency, individual and society, base and superstructure, nature and history, in a dialectical totality open to the future. The project is brought to its conclusion by means of critique, an a.